Preparation, Identification and analytical studies of some Metal Complexes with Schiff base ligand ( p-NPHAC) - Muna Abass Hadi (Al-Qadisiyah Journal of Pure Science, 2017)
Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) complexes containing a tetra dentate N2O2 ligand Î²-[(P-Nitro phenyl) azo]-2-(imino-4-antipyrinyl)-4-(2-imino- benzoic acid) pentane (p-NPHAC) have been preparation and characterization. The ligand was characterized on the basic of elemental analyses, FTIR, 1HNMR and electronic spectra studies while that the complexes were characterized by molar conductance, magnetic Susceptibility measurements, elemental analyses, FTIR and electronic spectra. The data show that the complexes have composition of [ML(H2O)2]Cl type. From analytical and spectral data of the complexes has been found to be (1:1) (metal:ligand). FTIR spectral data showed that the ligand behaves a tetra dentate moleculare with (N2O2) doner sequence to wards metal ions. Electronic spectra, magnetic susceptibility and FTIR spectral data of all the complexes suggest octahedral geometry around the central metal ion.